2011
DOI: 10.1159/000327344
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) Polymerase-1 Mediates Angiotensin II-Induced Expression of Plasminogen Activator Inhibitor-1 and Fibronectin in Rat Mesangial Cells

Abstract: Objective: To investigate the effects of poly(ADP-ribose) polymerase-1 (PARP-1) on angiotensin II (Ang II)-induced plasminogen activator inhibitor-1 (PAI-1) and fibronectin (FN) in rat mesangial cells (RMCs). Methods: Followed by serum starvation for 16 h, RMCs were exposed to Ang II for an indicated time to examine the protein expression of PARP-1. The cells were treated with or without Ang II for 12–24 h in the presence or absence of an inhibitor of PARP, N-(6-oxo-5,6-dihydrophenanthridin-2-yl)-N,N-dimethyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Aberrant activity and/or expression of PARP-1 are present in ECs under abnormally elevated levels of radical oxygen species (ROS), TNF-α, or angiotensin II to cause vascular inflammation (26)(27)(28). Such proinflammatory conditions are linked to decreases in AMPK activity and Bcl-6 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant activity and/or expression of PARP-1 are present in ECs under abnormally elevated levels of radical oxygen species (ROS), TNF-α, or angiotensin II to cause vascular inflammation (26)(27)(28). Such proinflammatory conditions are linked to decreases in AMPK activity and Bcl-6 expression.…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2) provides such a link between its dysregulation and pathogenesis of PH, suggesting that miR-19a/b may also contribute to PH via its target PAI-1. Previous studies shown that RAGE and PARP-1 are positive regulators of PAI-1 (47,58). We have found that miR-17~92 inhibits PAI-1 and RAGE, but not PARP-1 (Fig.…”
Section: L155mentioning
confidence: 55%